Communication of climate change and generation of adaptive capacities among farmers in the sub-humid tropics - Casanova-Pérez, Lorena; Martínez-Dávila, Juan Pablo; García-Alonso, Florencia; de la Cruz, Emigdio de la Cruz (Revista Mexicana de Ciencias Agrícolas, 2019)
This essay analyzes the importance of the communication of climate change in a specific local context, emphasizing the semantics used by the mass media influenced by a scientific-technical discourse. It also reflects on the opportunities to make said communication effective and convert climate change in a topic of social communication. The foregoing essentially required a documentary review of the role of the mass media in the communication of climate change and the principles of Luhmannian theory, as well as the use of previously generated information through a survey and in-depth interviews. The results show that the understanding of the meaning of climate change and its impacts on agriculture in the medium and long term requires considering semantics as a collective construction used in communicative operations by producers and their families in the local context, this will enable the generation of adaptive capacities and therefore, the design and implementation of proactive actions for the adaptation of agriculture in the Mexican subhumid tropics to climate change.